An analysis of language errors in diction in the entrepreneurship textbook "buku ajar untuk mahasiswa" by alexander hery - Aos Sogiri; Euis Eti Rohaeti; Wikanengsih (JLER (Journal of Language Education Research), 2026)
Textbooks have a significant effect on students in absorbing information and knowledge related to the field of science being studied. In addition, it can also be used as a reference in making a scientific paper. The content in the textbook is very important to pay attention to, especially in terms of language use. The language used in the textbook should be easy to understand and use effective sentences. This study aims to describe language errors in the field of diction. The method used in this research is descriptive qualitative using an error analysis framework. The data collection technique was carried out qualitatively. Data analysis was carried out with the following steps: processing and preparing data for analysis, reading and describing all data, recording all data obtained, analyzing in more detail and explaining errors in each data, classifying each data in the field of spelling or diction, and interpreting all relevant data. The results of the analysis show that there are 57 errors in diction. 41 language errors in error category, 2 lapses category, 14 mistake category.